The study of Phosphorus distribution at Putrajaya Wetland - Zahari N.M.; Abdul Malek N.F.F.; Fai C.M.; Haron S.H.; Zawawi M.H.; Ismail I.N.; Mohamad D.; Syamsir A.; Sidek L.M.; Ramli M.Z.; Ismail N.; Sapian A.Z.; et al. (Institute of Physics Publishing, 2023)
Aquatic organisms; Lakes; Phosphorus; Living things; Phosphorus distribution; Sampling stations; Total phosphorus; Trophic status; Water samples; Waterbodies; Wetlands